Creating and manipulating control flow graphs with multilevel grouping and code coverage - Sofokleous, Anastasis A.; Andreou, Andreas S.; Ioakim, Gianna (My University, 2006)
Various researchers and practitioners have proposed the use of control flow graphs for investigating software engineering aspects, such as testing, slicing, program analysis and debugging. However, the relevant software applications support only low level languages (e.g. C, C++) and most, if not all, of the research papers do not provide information or any facts showing the tool implementation for the control flow graph, leaving it to the reader to imagine either that the author is using third party software for creating the graph, or that the graph is constructed manually (by hand). In this paper, we extend our previous work on a dedicated program analysis architecture and we describe a tool for automatic production of the control flow graph that offers advanced capabilities, such as vertices grouping, code coverage and enhanced user interaction.
Keywords: Node grouping; Code coverage; Control flow graph